Прагматика второго лица - Kiklewicz, Aleksander (Acta Neophilologica, 2020)
The author considers the correlation between grammar and pragmatics as a problem of functional linguistics. The discussion focuses on pragmatic restrictions concerning the use of grammatical forms, i.e., the extent to which the grammatical meaning corresponds to the characteristics of speech acts. In this respect, the author analyzes Russian imperfective verbs in the second person of indicative. The analysis of the material collected from the Internet corpus of the Russian language demonstrates that the verbs in the 2nd person form are rarely used to implement the representative (assertive) speech acts. However, the use of verbs of the 2nd person in the general-personal, indefinite-personal and in the meaning of the 1st person is very common. The author concludes that the pragmatic-cultural factor is decisive in limiting the use of the verbs in the 2nd person form.